Characterization and Performance of Minimum Quantity Lubricants in Through-Tool Drilling (International Journal of Engineering Materials and Manufacture, 2020)
This study characterized airborne microdroplet diameters and size distribution from two commercially available lubricants A and B for internal minimum quantity lubrication (MQL). The effects of air pressure, oil channel size, physical properties of lubricants on the resultant microdroplets and through-tool MQL drilling performance were studied. Airborne microdroplet diameters were highly sensitive to the coolant channel sizes and air pressure. Cluster method was used to divide microdroplets into smaller clusters for comparison. Experimental data show that the average airborne microdroplet of lubricant B was larger than that of lubricant A at different air pressures and channel sizes. The contact angle of lubricant A was at least 10Â° less than that of lubricant B when depositing on glass or aluminium. High-speed imaging showed the tendency of more viscous lubricant B sticking to the drill tip, and higher pressure and longer time was required to atomize this viscous oil. Built-up-edges were less significant when drilling A380 aluminium with lubricant A. Due to high machinability of A380 aluminium, variation of hole diameter and hole cylindricity were minimal when drilling with different lubricants. Insignificant improvement in hole quality was observed when drilling with excessive amount of MQL lubricants or high concentration of lubricant C in flood coolant.